Comparison of Clinical Results of Pulsed Radio Frequency and Mixed Injection of Corticosteroid and Local Anesthetic in Patients with Shoulder Impingement Syndrome - Arman Taheri; Foad Fouladi; Alireza Khajenasiri; Reza Atef-Yekta; Nader-Ali Nazemian-Yazdi; Fatemeh Arjmandnia (Archives of Anesthesia and Critical Care)
Background: Shoulder impingement syndrome is a clinical situation that presenting with shoulder pain, difficultly and weakness. Present study designed for evaluating the effect of radiofrequency and corticosteroid injection in longterm treatment follow up for pain reduction and functional evaluation of shoulder joint. Methods: Sixty patients were analyzed equally in two treatment groups. Post-treatment follow up at one, four and twelve weeks after procedures were carried out using Visual Analog Scale (VAS) for pain relief, Shoulder Pain and Disability Index (SPADI) for shoulder function and Beck Depression Inventory (BDI). Results: Both treatment groups showed significantly pain reduction (P-value<0.001 for both) in 4 weeks after procedures. In time point comparison between 4 to 12 weeks postoperatively, there were significantly reduced pain in R group (P=0.03), but not significant in C group (P=0.1). Total SPADI score was significantly lower in RF group in time points 1 and 4 weeks (P<0.001), but not significant in 12 weeks of follow up. Conclusion: Radiofrequency could not be sufficient alone for retrieving function of the shoulder at the long periods of time after procedure, unless good and effective results for first 1 and 4 weeks of follow up.